The Impact of E-Wallet Effectiveness and Efficiency in Financial Management for Mataram University Students Who Participate in the Independent Student Exchange - Rengganis, Fadia Maya; Lestari, Baiq Anggun Hilendri (PT FORMOSA CENDEKIA GLOBAL, 2024)
An innovation that is currently experiencing development in the financial sector is the existence of an E-Wallet, which is expected to be able to be used effectively and efficiently in managing student finances well. This research aims to determine the impact of the effectiveness and efficiency of using E-Wallets in managing finances for Mataram University students who take part in the Independent Student Exchange 3 program. This research uses quantitative research methods with descriptive statistical research. The population in this study were students who took part in the Independent Student Exchange Program 3, Mataram University. Samples were taken using a purposive sampling method with a sample size of 84 respondents. The research results obtained from data analysis show that effectiveness and efficiency partially have a positive and significant effect on the use of e-wallets in managing the finances of PMM 3 Students at Mataram University.